Crustal thickness anomalies in the North Atlantic Ocean basin from gravity analysis - Wang, Tingting; Lin, Jian; Tucholke, Brian; Chen, Yongshun John (Geochemistry, Geophysics, Geosystems, 2011)
Gravity-derived crustal thickness models were calculated for the North Atlantic Ocean between 76 degrees N and the Chain Fracture Zone and calibrated using seismically determined crustal thickness. About 7% of the ocean crust is < 4 km thick (designated as thin crust), and 58% is 4-7 km thick (normal crust); the remaining 35% is > 7 km thick and is interpreted to have been affected by excess magmatism. Thin crust probably reflects reduced melt production from relatively cold or refractory mantle at scales of up to hundreds of kilometers along the spreading axis. By far the most prominent thick crust anomaly is associated with Iceland and adjacent areas, which accounts for 57% of total crustal volume in excess of 7 km. Much smaller anomalies include the Azores (8%), Cape Verde Islands (6%), Canary Islands (5%), Madeira (< 4%), and New England-Great Meteor Seamount chain (2%), all of which appear to be associated with hot spots. Hot spot-related crustal thickening is largely intermittent, suggesting that melt production is episodic on time scales of tens of millions of years. Thickened crust shows both symmetrical and asymmetrical patterns about the Mid-Atlantic Ridge (MAR) axis, reflecting whether melt anomalies were or were not centered on the MAR axis, respectively. Thickened crust at the Bermuda and Cape Verde rises appears to have been formed by isolated melt anomalies over periods of only similar to 20-25 Myr. Crustal thickness anomalies on the African plate generally are larger than those on the North American plate; this most likely results from slower absolute plate speed of the African plate over relatively fixed hot spots. Geochemistry & Geophysics SCI(E) EI 6 ARTICLE 3 null 12